Кубинское каприччио: [роман] / Чингиз Абдуллаев - Абдуллаев Чингиз Акифович (Эксмо, 2007)
Экземпляры: ф.1 (20200204☮) / Инвентарный номер: 58439 / Цена: 20.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А13 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6